Environmental health research challenges in Africa: Insights from symposia organized by the ISEE Africa Chapter at ISES-ISEE 2018. Issue 6 (December 2019) - Koné, Brama; Oulhote, Youssef; Mustapha, Adetoun; Olaniyan, Toyib; Kouame, Kouadio; Benmarhnia, Tarik; Munyinda, Nosiku; Basu, Nil; Fobil, Julius N.; Etajak, Samuel; Annesi-Maesano, Isabella; Chevrier, Jonathan; et al.
Abstract : Supplemental Digital Content is available in the text.